Fracture resistance of teeth restored with bulk-fill and fiber-reinforced composites in class II cavities = Resistencia a la fractura de dientes restaurados con resinas de relleno y resinas reforzadas con fibra en cavidades clase II - Keskin, Gül
This study aimed to evaluate the fracture resistance of teeth restored with conventional, bulk-fill, and fiber-reinforced composite materials regarding intact teeth. Standard cavities were prepared on 70 sound third molar teeth. The teeth were randomly divided into six groups: intact teeth, conventional Bis-GMA based composite, fiber-reinforced composite, Bis-GMA based bulk-fill composite, ormocer based bulk-fill composite, glass containing resin-based bulk-fill composite. The data was obtained by a Universal Testing Machine and analyzed statistically. Fracture resistance of the teeth restored with conventional composite was significantly lower than the other groups (p<0.05). The teeth restored with fiber-reinforced composite showed the highest fracture resistance; however, there were no statistically significant differences between intact teeth and teeth restored with fiber-reinforced composite, Bis-GMA based bulk-fill composite, and glass containing resin-based bulk-fill composite (p>0.05). The obtained data showed that restoring teeth with bulk-fill and fiber-reinforced composites could be recommended in Class II cavities.